2016
DOI: 10.1021/acsami.6b00877
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chromium and Niobium Doping on the Morphology and Electrochemical Performance of High-Voltage Spinel LiNi0.5Mn1.5O4 Cathode Material

Abstract: Undoped, Cr-doped, and Nb-doped LiMn(1.5)Ni(0.5)O4 (LNMO) is synthesized via a PVP (polyvinylpyrrolidone)-combustion method by calcinating at 1000 °C for 6 h. SEM images show that the morphology of LNMO particles is affected by Cr and Nb doping. Cr doping results in sharper edges and corners and smaller particle size, and Nb doping leads to smoother edges and corners and more rounded and larger particles. The crystal and electron structure is investigated by XRD- and synchrotron-based soft X-ray absorption spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(45 citation statements)
references
References 45 publications
2
42
0
1
Order By: Relevance
“…The substitution of Mn and Ni by cations, such as Al 3+ , Co 3+ , can also stabilize the structure of LNMO and eliminate the formation of Li y Ni 1− y O impurity phase . Mao et al synthesized Cr doped LNMO via a PVP (polyvinylpyrrolidone) combustion method by calcinating at 1000 °C for 6 h. Yang et al prepared Cr doped LNMO by adopting a soft combustion reaction with benzoyl peroxide as the oxidizer, followed by calcination at 800 °C for 20 h. Li et al prepared Cr 0.05 Ni 0.225 Mn 0.725 (OH) 2 precursors by a coprecipitation method, the precursors were mixed with Li 2 CO 3 followed by heating at 950 °C for 6 h and then at 730 °C for another 3 h. They focused on the elimination of Li y Ni 1− y O impurity phase and improvement of structure stability using Cr doping. Herein, we report the unique characteristic of Cr 3+ to substitute the Ni and Mn ion to improve the electrochemical performance of LNMO, especially the cycling performance at low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The substitution of Mn and Ni by cations, such as Al 3+ , Co 3+ , can also stabilize the structure of LNMO and eliminate the formation of Li y Ni 1− y O impurity phase . Mao et al synthesized Cr doped LNMO via a PVP (polyvinylpyrrolidone) combustion method by calcinating at 1000 °C for 6 h. Yang et al prepared Cr doped LNMO by adopting a soft combustion reaction with benzoyl peroxide as the oxidizer, followed by calcination at 800 °C for 20 h. Li et al prepared Cr 0.05 Ni 0.225 Mn 0.725 (OH) 2 precursors by a coprecipitation method, the precursors were mixed with Li 2 CO 3 followed by heating at 950 °C for 6 h and then at 730 °C for another 3 h. They focused on the elimination of Li y Ni 1− y O impurity phase and improvement of structure stability using Cr doping. Herein, we report the unique characteristic of Cr 3+ to substitute the Ni and Mn ion to improve the electrochemical performance of LNMO, especially the cycling performance at low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…There could be seen the good agreement between the experimental and calculated results (R e < 5%, R p < 4%), which proves that the structural model is reasonable. 31 Besides, the lattice parameter a and c of the NCM sample is 2.8715 and 14.2008Å. Aer Co doping, a and c increase to 2.8719 and 14.2019Å, respectively.…”
Section: Resultsmentioning
confidence: 92%
“…Jing et al [70] synthesized undoped, Cr-doped, and Nb-doped LNMO via a polyvinylpyrrolidone combustion method by calcinating at 1000 °C for 6 h. Scanning electron microscopy (SEM) images showed that Cr doping resulted in sharper edges and corners and smaller particle size (Fig. 4a), while Nb doping led to smoother edges and corners and more rounded and larger particles (Fig.…”
Section: Approaches To Improve the Cycling Stability Of Lnmomentioning
confidence: 99%
“…4SEM images of a Cr doping and b Nb doping, c rate cycle performance and d cycle performance of all samples. Nb-0.02: LiNb 0.02 Ni 0.49 Mn 1.49 O 4 , Nb-0.04: LiNb 0.04 Ni 0.48 Mn 1.48 O 4 , Cr-0.1: LiCr 0.1 Ni 0.45 Mn 1.45 O 4 , Cr-0.2: LiCr 0.2 Ni 0.4 Mn 1.4 O 4 [70] …”
Section: Approaches To Improve the Cycling Stability Of Lnmomentioning
confidence: 99%
See 1 more Smart Citation